UJI VALIDASI TERMAL VIBRASI UNTUK MUATAN MISI MIKROSAT - Syah, Agus Harno Nurdin (Indonesian Journal of Aerospace, 2004)
To launching a spacecraft (rocket and satellite) including all of the systems, some rules and regulation of validation test for all the spacecraft systems is needed. Validation test mentioned is done to find out the ability of all the systems to the environmental influences of the external although internal with measurements simultaneously done. This is including possibilities the operating all of the electronic systems and epending the life times, operation time of the internal and external condition to the parameters effect of environmental the spacecraft systems. Thermal vibration is two parameters effect of environmental which would receiped simultaneously by the microsatellite or spacecraft on trajectory time when the spacecraft inside of the thermospheer zone at height about (80-500) km and the exospher zone at height about (500-1000)km under the seal level. Therefore, thermal vibration test is very important to do before a spacecraft or microsatellite would be launched, because the environmental parameters is very dangerous to the microsatellite or spacecraft mission payload.